2011
DOI: 10.1038/aps.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of CrTX in human lung adenocarcinoma cell line A549

Abstract: Aim: To assess the cytotoxic effect of crotoxin (CrTX), a potent neurotoxin extracted from the venom of the pit viper Crotalus durissus terrificus, in human lung adenocarcinoma A549 cells and investigated the underlying mechanisms. Methods: A549 cells were treated with gradient concentrations of CrTX, and the cell cycle and apoptosis were analyzed using a flow cytometric assay. The changes of cellular effectors p53, caspase-3 and cleaved caspase-3, total P38MAPK and pP38MAPK were investigated using Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Crotoxin, a noncovalent complex (formed by two nonidentical subunits: a basic PLA 2 crotoxinB and a nonenzymatic acidic crotoxinA) isolated from the venom of Crotalus durissus terrificus, exhibits a preferential cytotoxic activity against various types of tumor cells including K-562 cells [58], MCF-7 cells [59] and lung adenocarcinoma A549 cells. Treatment of A549 cells with crotoxin significantly inhibited the cell growth in a dose-dependent manner and displayed anti-angiogenic effects in vitro [60]. Crotoxin has been used in the treatment of different advanced carcinomas [61].…”
Section: Discussionmentioning
confidence: 99%
“…Crotoxin, a noncovalent complex (formed by two nonidentical subunits: a basic PLA 2 crotoxinB and a nonenzymatic acidic crotoxinA) isolated from the venom of Crotalus durissus terrificus, exhibits a preferential cytotoxic activity against various types of tumor cells including K-562 cells [58], MCF-7 cells [59] and lung adenocarcinoma A549 cells. Treatment of A549 cells with crotoxin significantly inhibited the cell growth in a dose-dependent manner and displayed anti-angiogenic effects in vitro [60]. Crotoxin has been used in the treatment of different advanced carcinomas [61].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that CrTX-induced cell apoptosis in human lung adenocarcinoma A549 cells by activating p38MAPK and caspase-3. We have also demonstrated CrTXinduced cell cycle arrest mediated by increased wt p53 expression and p-JNK up-regulation in SK-MES-1 cells [24,25] . However, the molecular mechanisms involved in the inhibition of SK-MES-1 cells, specifically the effect of p38 on the induction of apoptosis and autophagy, are not well characterized.…”
Section: Introductionmentioning
confidence: 89%
“…Despite the neurotoxicity, several studies have pointing towards other biological activities of CTX that have potential pharmacological value such as immunomodulatory, anti-nociceptive, anti-inflammatory, anti-tumoral and anti-microbial activities (Sampaio et al, 2010;Favoretto et al, 2011;Ye et al, 2011;Wang et al, 2012;He et al, 2013;Han et al, 2014;Almeida et al, 2015;Brigatte et al, 2016;Faure et al, 2016). Thus, a more complete understanding of the neurotoxic action of CTX is relevant not only to improve the treatment of envenomation, but also to enable the biotechnological use of this toxin or new drugs derived from this protein.…”
Section: Introductionmentioning
confidence: 99%